2022
DOI: 10.1038/s41598-022-13695-z
|View full text |Cite
|
Sign up to set email alerts
|

Phoenixin-14 alters transcriptome and steroid profiles in female green-spotted puffer (Dichotomyctere nigroviridis)

Abstract: Phoenixin (PNX) is a highly conserved, novel hormone with diverse functions, including hypothalamic control of reproduction, appetite modulation, and regulation of energy metabolism and inflammation. While some functions appear conserved across vertebrates, additional research is required to fully characterize these complex pleiotropic effects. For instance, very little is known about transcriptome level changes associated with PNX exposure, including responses in the hypothalamic–pituitary–gonadal (HPG) axis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…In zebrafish, PNX-20 stimulates steroidogenesis: it increases the mRNA expression of many steroidogenic factors, including cyp11a1 , cyp17a1 , cyp19a1 , and 17bhsd , as well as er2a and er2b in the ovary [10]. In contrast, Breton et al [37] performed transcriptome and steroid profiles in female green-spotted puffer ( Dichotomyctere nigroviridis ) and found that steroidogenic enzymes are largely unaffected by PNX-14 treatment. Although they found that PNX-14 administration increased the blood P 4 levels in females, these changes were not significant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In zebrafish, PNX-20 stimulates steroidogenesis: it increases the mRNA expression of many steroidogenic factors, including cyp11a1 , cyp17a1 , cyp19a1 , and 17bhsd , as well as er2a and er2b in the ovary [10]. In contrast, Breton et al [37] performed transcriptome and steroid profiles in female green-spotted puffer ( Dichotomyctere nigroviridis ) and found that steroidogenic enzymes are largely unaffected by PNX-14 treatment. Although they found that PNX-14 administration increased the blood P 4 levels in females, these changes were not significant.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, PNX expression has been demonstrated in the ovary of rodents [ 7 , 9 ], chickens [ 33 ], and humans [ 7 ], while GPR173 has been detected in rodents [ 7 , 9 , 13 , 34 ], cattle [ 35 ], and humans [ 7 , 36 ]. The PNX/GPR173 system has also been described extensively in fish [ 8 , 10 , 37 ]. More precisely, in both human and mouse ovaries, PNX/GPR173 signals have been detected in Gc and theca cells (Tc), and prominently in oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve libraires were sequenced using the Illumina NovoSeq 6000 following methods outlined in [1] . A bioinformatics pipeline described in the methods below identified transcripts differentially expressed in response to broflanilide.…”
Section: Data Descriptionmentioning
confidence: 99%
“…RNA library construction followed instructions outlined in the NEBNextⓇ Ultra™ II Directional RNA Library Prep Kit for IlluminaⓇ (New England Biolabs, catalog #E7760). Libraries were sequenced using the Illumina NovoSeq 6000 followed methods outlined in [1] . Data format Raw Analyzed Filtered Description of data collection Fold changes and p-value for all transcripts were generated using and mapped into Pathway Studio 12.0 (Elsevier).…”
mentioning
confidence: 99%